Photothermal nanohybrid hydrogels for biomedical applications - Ding, Fan; Zhang, Linlin; Chen, Xu; Yin, Weiling; Ni, Li; Wang, Miao (Frontiers in Bioengineering and Biotechnology, 2022)
In the past decades, diseases such as wound infection, cancer, bone defect and osteoarthritis have constantly threatened the public health. However, the traditional treatment has many defects, such as high cost, easy recurrence and high biological toxicity. Hydrogel is a material with three-dimensional network structure, which has a series of advantages, such as injectability, self-healing, easy loading and control of drug release, and excellent biocompatibility. Therefore, it is extensively used in drug delivery, antibacterial, anti-cancer and other fields. However, the traditional hydrogels have a single performance, and often rely on the drugs loaded on them to cure diseases, which cannot achieve sustainable therapeutic effect. In order to solve this problem, photothermal nano hydrogel has become an ideal material due to its excellent physical and chemical properties. Photothermal nano hydrogels based on photothermal therapy (PTT) can use the photothermal effect of photothermal agent (PTA) to increase local temperature and control the sol-gel phase transition behavior of hydrogels, so they are widely used in drug release, photothermal sterilization, photothermal inhibition of cancer cells and enhancement of bone repair. To sum up, this paper introduces the photothermal nanomaterials used in the preparation of hydrogels, and discusses their applications in the fields of drug release, photothermal sterilization, photothermal cancer cell inhibition and enhanced bone repair.